Student-Centered Interpretation and Expression in the Large-Group Secondary Band Class - (:unkn) unknown (My University, 2014)
In this study, the learner-centered instruction of the interpretation of expressive elements in a large-group band class is closely examined in order to determine if secondary-level students primarily learning in a large-group setting are able to utilize their own interpretations in applying expressive elements to their own performances. During the spring of 2014, a focus group of 11 students from an eighth-grade band in southeastern Wisconsin were assessed by a panel of six evaluators who are experienced Wisconsin band directors. Evaluations consisted of audio-recorded performances of two short melodies, one being actively studied in the large-group classroom setting and one not being rehearsed, before and after a nine-week teaching period. Using a mixed-method approach, quantitative scores and qualitative comments were received from evaluators for each pre- and post-treatment performance. In addition, qualitative feedback was gathered from student written reflections and formative teacher observations. Results indicated student growth in overall levels of expression and interpretation, as well the clarity of all expressive elements (rubato, dynamic contrast, and tension and release) focused upon during the study in both compositions. The amount of growth, however, was not as large in the composition not being rehearsed in the classroom setting.
Keywords: Band; Expression; Expression Pedagogy; Interpretation; Student-Centered Instruction